2016
DOI: 10.3389/fpsyg.2016.01841
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal Modulates Attentional Bias to Angry Faces

Abstract: Heightened attentional bias to emotional information is one of the main characteristics of disorders related to emotion dysregulation such as anxiety, depression, and substance abuse. Although reappraisal, an emotion regulation strategy, is known to effectively modulate subjective experience of emotions, it remains unknown whether reappraisal can alter attentional biases to emotional information. In the current research, we investigated the influence of instruction-induced state reappraisal (Study 1) and trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Jamieson, Nock, and Mendes (2012) found that changes in cognitive appraisal of a stress task could improve cardiovascular function and reduce attentional bias to negative stimuli. Kim, Kim, and Kim (2016) found that participants' attentional bias toward anger pictures decreased after reducing cognitive appraisal of the negative emotion, and that such bias increased after increasing cognitive appraisal of the negative emotion. Accordingly, we hypothesized that cognitive appraisal would moderate the relationship between state anxiety and attentional bias (Hypothesis 3, H3).…”
mentioning
confidence: 94%
“…Jamieson, Nock, and Mendes (2012) found that changes in cognitive appraisal of a stress task could improve cardiovascular function and reduce attentional bias to negative stimuli. Kim, Kim, and Kim (2016) found that participants' attentional bias toward anger pictures decreased after reducing cognitive appraisal of the negative emotion, and that such bias increased after increasing cognitive appraisal of the negative emotion. Accordingly, we hypothesized that cognitive appraisal would moderate the relationship between state anxiety and attentional bias (Hypothesis 3, H3).…”
mentioning
confidence: 94%
“…Several analyses were carried out on the dot probe reaction time (RT) data. Initially, all incorrect responses were excluded as well as RTs less than 200 ms, which were considered so short as to be guesses (see also Britton et al, 2013;Kim, Kim, & Kim, 2016;Miloff, Savva, & Carlbring, 2015;Reynolds et al, 2014Reynolds et al, , 2018. Log RTs were used to adjust for large outliers (see Ratcliff, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, individual differences in the habitual use of emotion regulation strategies are related to the modulation of these forms of affective processing, contributing to maladaptive stress regulation. The habitual use of reappraisal, a strategy typically associated with enhanced stress recovery [18], has been found to modulate attention directed to negative information [19]. Further, the momentary use of reappraisal has been found to predict higher positive interpretation biases to solve ambiguities [20].…”
Section: Introductionmentioning
confidence: 98%